2008
DOI: 10.1158/1078-0432.ccr-07-1835
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Crypt Foci as Precursors of the Dysplasia-Carcinoma Sequence in Patients with Ulcerative Colitis

Abstract: Purpose: Long-standing ulcerative colitis (UC) predisposes patients to the development of colorectal cancer, but surveillance of colitis-associated cancer by detecting the precancerous lesion dysplasia is often difficult because of its rare occurrence and normal-looking appearance. In sporadic colorectal cancer, aberrant crypt foci (ACF) have been reported by many investigators to be precursor lesions of the adenoma-carcinoma sequence. In the present study, we analyzed the genetic background of ACF to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…There were significant correlations between the number of ACF, the presence of dysplastic ACF, ACF size, and the number of adenomas, as well as the provocative findings of a reduction in ACF in a substudy of the effects of a nonsteroidal anti-inflammatory drug that are discussed later. Stimulated by this Japanese study, investigations of ACF and their potential use as a surrogate endpoint of clinical prevention trials proceeded rapidly (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…There were significant correlations between the number of ACF, the presence of dysplastic ACF, ACF size, and the number of adenomas, as well as the provocative findings of a reduction in ACF in a substudy of the effects of a nonsteroidal anti-inflammatory drug that are discussed later. Stimulated by this Japanese study, investigations of ACF and their potential use as a surrogate endpoint of clinical prevention trials proceeded rapidly (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…These results are consistent with the hypothesis that age-related methylation marks (and may lead to) the field defect that reflects acquired predisposition to colorectal neoplasia. More recently, Kukitsu et al (Kukitsu et al, 2008) identified hypermethylation and subsequent reduced p16 gene expression in aberrant crypt foci (ACF) in UC. These are the earliest detectable lesions in the CACRC pathway and suggest that aberrant methylation of tumour suppressor genes may also be an early event in CACRC carcinogenesis 3. Who, when and how to screen?…”
Section: Dna Methylationmentioning
confidence: 99%
“…These results are consistent with the hypothesis that age-related methylation marks (and may lead to) the field defect that reflects acquired predisposition to colorectal neoplasia. More recently, Kukitsu et al (2008) identified hypermethylation and subsequently reduced p16 gene expression in aberrant crypt foci (ACF) in UC. These are the earliest detectable lesions in the CACRC pathway and suggest that aberrant methylation of tumour suppressor genes may be an early event in CACRC carcinogenesis.…”
Section: Dna Methylation and Transcriptional Silencingmentioning
confidence: 99%